Design And Analysis Of Water Quality Based On Electrical And Optical Sensing - Nur Afiqah Binti Razman
Water is the most important necessities for living things. Water pollution always occurs in Malaysia due to activities and waste products from industries, constructions, agriculture, and household. Water pollutions disturb water supply and inhibit activities like household and economies. Therefore, water quality monitoring systems are needed to assist in mitigating pollution issues. This research aims to monitor the quality of water from different water sources (tap, river, and lake) with objectives: (1) to develop water quality monitoring system based on pH, temperature, turbidity, electrical conductivity, and oxidation-reduction potential parameters using electronic sensing techniques, (2) to investigate water turbidity using optical sensing and spectroscopy techniques and (3) to analyse data from the system based on analysis of variance test. This research is divided into three parts. The first part is the electronic sensing water quality monitoring system. pH, temperature, turbidity, EC and ORP electronic sensors were connected to microcontroller to develop the monitoring system and the results were made available on the internet by using ESP8266 Wi-Fi module and ThingSpeak, an Internet of Thing platform for real-time and continuous water monitoring. Lake water samples gave the highest value in pH, temperature and turbidity while tap water gave highest oxidation-reduction potential and electrical conductivity results. The second part is the spectroscopy water turbidity monitoring technique. The absorbance, transmittance and fluorescence of water samples were observed using two spectrometers: Near-Infrared spectrometer and Visible Near-Infrared spectrometer. The lake water samples gave the highest absorbance and fluorescence spectra while tap water samples gave the highest transmittance spectra. The third part of the research is the optical sensing water quality monitoring system. An optical Charge-coupled device (CCD) linear sensor (SONY ILX551a) was used in this system. The light source, a laser diode was pointed to a clear container (containing water samples) for light to propagate through it. The sensor detected and changed the output light to voltage values. Tap water samples give the highest output voltages. Water samples with higher turbidity give low charge-coupled device linear sensor voltage outputs demonstrating the system’s ability to determine the turbidity of water. Analysis of variance (ANOVA) test was done to validate the results from the systems. Each electronics and optical sensing techniques have advantages and disadvantages. This research can be used as a reference to develop a reliable and good water quality monitoring system. Further enhancement can be made by developing a real-time and continuous optical sensing water monitoring system.